ENHANCING EXPRESSIVE COMMUNICATION IN CHILDREN WITH AUTISM SPECTRUM DISORDER THROUGH THE USE OF THE PICTURE EXCHANGE COMMUNICATION SYSTEM (PECS) COMBINED WITH ANIMATED VIDEO - Rina Mariyana; Neila Sulung; Evi Hasnita; Endang Dian Pratiwi (LLDIKTI Wilayah X, 2026)
Children with autism generally experience barriers in communication skills so they need appropriate interventions to support the development of these abilities. One of the approaches that is considered effective in improving communication skills is the Picture Exchange Communication System (PECS) assisted by animated videos. This study aims to analyze the effect of the application of PECS assisted by animated videos on the communication ability of children with autism at SLB Autisma YPPA Bukittinggi. This study uses a quasi-experimental design with a pretest-posttest design. The research was carried out in September 2024 with a sample of 28 children selected using purposive sampling techniques. The research instrument was in the form of a communication ability questionnaire. Data analysis is carried out using appropriate statistical tests. The results showed that the average communication ability score of children with autism before the intervention was 27.36 and increased to 47.29 after the intervention. The results of the statistical test showed a value of p = 0.001 (p < 0.05), which indicates a significant influence of the application of PECS assisted by animated videos on the communication ability of children with autism. It can be concluded that PECS assisted by animated videos is effective in improving the communication skills of children with autism. This method is expected to be used as an alternative learning model in an effort to improve the communication skills of children with autism.